”Jos et aloita, mikään ei muutu”: Tulevaisuuksien rakentuminen median sijoitusdiskursseissa - Lillqvist, Ella; Porttikivi, Merja (VAKKI ry, 2023)
Over the past few years, individuals have become increasingly interested in investing and this investment boom is also reflected in news media content. Investing is an activity based on predictions and expectations about the future that seeks to actively influence accumulation of wealth and thus one’s own future. This study focuses on imagined futures in investment discourse and the performative role of imagined futures in the construction of financial markets and market society as a whole. The data spans the years 2015–2022 and consists of a 1.2-million-word corpus of articles and reader comments from four Finnish newspapers. This corpus is analysed using corpus-assisted discourse studies, combining quantitative and qualitative text analysis. In the light of the material, the future is imagined both from an individual perspective and from broader global or societal perspectives. Investors’ individualistic futures are mainly imagined as positive and can therefore motivate people to invest. Broader visions of the future are more negative, for example the idea that in the future society will not afford to pay pensions, which in turn requires the individual to prepare through investing. The investor is predominantly seen as a neoliberal subject who takes responsibility and is able to influence their own future.
Keywords: korpusavusteinen diskurssintutkimus; kuvitellut tulevaisuudet; lehdistö; performatiivisuus; sijoittaminen; verkkouutisten kommenttipalstat; fi=Viestintätieteet|en=Communication Studies|